Sonication-Assisted Agrobacterium-mediated Gene Transformation of Oil Palm Secondary Somatic Embryo - Yenchon , Sureerat; Te-chato, Sompong (Agriculture and Natural Resources, 2015)
The inﬂ uence was investigated of the hygromycin concentration on the survival rate of oil palm secondary somatic embryos (SSEs) and sonication-assisted Agrobacterium-mediated transformation (SAAT). The results showed that 20 mg.L-1 hygromycin could completely inhibit growth of SSEs, suitable for selection of transformed SSEs. The transient ß-glucuronidase (gus) expression was affected by the different period of SAAT which was signiﬁ cantly enhanced by increasing the period of SAAT. However, the longer exposure to SAAT caused a decrement in the frequency of plantlet regeneration. The highest transformation efﬁ ciency was obtained when the SSEs were sonicated for 5 min. Polymerase chain reaction and Southern blot hybridization analysis conﬁ rmed the presence of the reporter genes in the transformed plantlet genome.